FoveAR: Combining an Optically See-Through Near-Eye Display with Spatial Augmented Reality Projections - Benko, Hrvoje; Ofek, Eyal; Zheng, Feng; Wilson, Andy (UIST '15 Proceedings of the 28th Annual ACM Symposium on User Interface Software & Technology, 2015)
Optically see-through (OST) augmented reality glasses can overlay spatially-registered computer-generated content onto the real world. However, current optical designs and weight considerations limit their diagonal field of view to less than 40 degrees, making it difficult to create a sense of immersion or give the viewer an overview of the augmented reality space. We combine OST glasses with a projectionbased spatial augmented reality display to achieve a novel display hybrid, called FoveAR , capable of greater than 100 degrees field of view, view dependent graphics, extended brightness and color, as well as interesting combinations of public and personal data display. We contribute details of our prototype implementation and an analysis of the interactive design space that our system enables. We also contribute four prototype experiences showcasing the capabilities of FoveAR as well as preliminary user feedback providing insights for enhancing future FoveAR experiences.